Avaliação da atividade anti-inflamatória e antinociceptiva do alcaloide curina em modelos experimentais de inflamação aguda e nocicepção - Leite, Fagner Carvalho (2012)
The alkaloids represent the largest single class of secondary metabolites of plants and they have a range of pharmacological activity, such as: emetic, anti-cholinergic, antitumor, diuretic, sympatho-mimetic, antiviral, antihypertensive, analgesic, antidepressant, mio-relaxant, anti-tussigen, antimicrobial and anti-inflammatory activities. Curine is a major bisbenzylisoquinoline alkaloid isolated from Chondodendron platyphyllum (Menispermaceae). This alkaloid presented immunomodulatory effects in experimental model of allergic inflammation. In order to evaluate the anti-inflammatory and antinociceptive activities of curine different experimental models of acute inflammation and experimental models of pain sensitivity (nociception) were used: paw edema formation induced by carrageenan, zymosan, LPS, prostaglandin E2 (PGE2) and bradykinin, vascular permeability induced by acetic acid, NO production by J774.A1 cells, cell migration and cytokines/chemokines (TNF-α, IL-1β , IL-6, MCP-1 and KC) production in a mice model of LPS-induced pleurisy, abdominal writhing, formalin test and LPS-Induced hyperalgesia. The results showed that curine significantly reduced (p<0,05-0,001) the paw edema evoked by carrageenan, zymosan, LPS and prostaglandin E2. However, without any influence on the bradykinin induced edema, reduced the increase in vascular permeability induced by acetic acid, inhibits LPS/IFNγ-induced NO production in J774.A1 cells, reduced neutrophil recruitment and attenuated levels of TNF-α, IL-6, MCP-1 e KC into the pleural cavity. In abdominal writhing induced by acetic acid, curina was significantly effective (p<0,05), increasing the latency to first writhing and decreasing the number of writhings. In both phases of formalin test, curine was able to significantly reduced (p<0,05-0,001) time to paw licking, besides increasing the latency to thermal stimuli perception in LPS-induced hyperalgesia in the hot-plate test. Therefore, this study demonstrated that curine has anti-inflammatory and antinociceptive activities by inhibiting the action of both cells and molecules involved in inflammatory process and inflammatory pain.